Violência Clerical: abuso sexual de mulheres por padres no Brasil - Jurkewicz, Regina Soares (2006)
This thesis examines sexual abuse and violence against women by priests. Using public complaints made in Brazil between 1994 and 2000 as an empirical base, it details 203 articles related to 21 cases of sexual misconduct by clergymen, including sexual abuse, rape, and the violation of vows of celibacy. These articles were grouped to create a dossier on each of the cases and numbered sequentially. Brazil´s most important media sources were consulted, including online news sites and non-governmental organizations (NGOs) across the country. Two representative cases were chosen and studied in depth. Interviews were conducted with plaintiffs, witnesses, members of the Church hierarchy, and attorneys involved in the cases, preserving the anonymity of all interviewees. Utilizing a sociological perspective, the analysis explores the mechanisms by which the Catholic Church attempts to cover up such cases. Showing the specificities of the violence perpetrated against women by priests, the study points toward the existence of structural causes of this violence and their different manifestations, examining them through the lens of feminist theory. The study suggests that a specific analytic category should be developed in order to better comprehend this particular type of violence against women. The term clerical violence is proposed for describing this type of violence, whose structural aspects include gender asymmetries, the separation between clergy and lay members, patriarchal discourse, the sexualization of ministerial relations and the force of symbolic violence. The work of Pierre Bourdieu is useful in understanding religion as a symbolic system that endows the priest with sacred power. Given that the causes of clerical violence are mainly structural, likewise, structural solutions are needed in addressing the issue